Influence of MgO content on the thermo-physical properties of CaO-Al2O3-MgO-FexO-SiO2-K2O slags - HOU Peng-tao; WANG Li-jun; LIU Shi-yuan; ZHANG Jian-kun; CHOU Kuo-chih (工程科学学报)
The effects of MgO content on the viscosity and melting behaviors of CaO-Al2O3-MgO-FexO-SiO2-K2O slags were studied. The slag samples were characterized by X-ray diffraction (XRD) and scanning electron microscopy (SEM) to identify precipitated phases during the cooling process. Meanwhile, theoretical calculations on the viscosities, solidus/liquidus temperatures as well as quantities of various precipitated phases from the slag system were also carried out by using the FactSage software, which were compared with the experimental results. The results indicate that the addition of MgO in slag could cause the increase of melting temperature. The relation between viscosities and temperature presents a breakpoint where the viscosity has a rapid rise, and above this transition temperature, MgO content has little effect on the viscosity. The transition temperature increases with the increasing of MgO content. In the process of slag cooling, the crystalline phases are mainly composed of olivine and spinel. From the calculation results, it could be found that the addition of MgO enhances the precipitates of olivine, which makes the viscosity increase suddenly.